Comparison Study of Two Different Sun-Tracking Methods in Optical Efficiency of Heliostat Field - K.-K. Chong; M. H. Tan (International Journal of Photoenergy)
There are two sun-tracking methods widely used for the heliostat, which are conventional Azimuth-Elevation and revolutionary Spinning-Elevation methods. Following the previous study to compare the range of motion, a comparison study in optical efficiency of heliostat field for the two methods is further explored in this paper. A special algorithm using ray-tracing technique has also been developed to simulate the optical efficiency of heliostat field for both sun-tracking methods in different latitudes. With the new algorithm, comprehensive analysis to compare the optical efficiency of individual heliostat and the overall heliostat field for the two sun-tracking methods has been carried out.